2010
DOI: 10.1161/atvbaha.110.206185
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine Osteogenic Signals via Bone Morphogenetic Protein-2 Accelerate the Atherosclerotic Intimal Calcification In Vivo

Abstract: Objective-Vascular calcification is an important risk factor for cardiovascular diseases. Here, we investigated a role of dedifferentiated vascular smooth muscle cells (VSMCs) in the atherosclerotic intimal calcification. Methods and Results-We prepared human cultured VSMCs in either redifferentiatiated or dedifferentiated state and analyzed the gene expressions of bone-calcification regulatory factors. Expression of bone morphogenetic protein-2 (BMP-2), a potent initiator for osteoblast differentiation, was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 59 publications
3
105
0
Order By: Relevance
“…Furthermore, we demonstrated that RANKL stimulates Pi-induced cardiac fibroblast calcification in vitro via the activation of osteogenic signals, such as BMP2, SPARC, Runx2, Fra-1, and NF-kB (38)(39)(40)(41). Taken together, our present data as well as previous findings suggest that inflammation or inflammatory cytokines may be involved in the entire process of soft-tissue calcification by CVB3 infection.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, we demonstrated that RANKL stimulates Pi-induced cardiac fibroblast calcification in vitro via the activation of osteogenic signals, such as BMP2, SPARC, Runx2, Fra-1, and NF-kB (38)(39)(40)(41). Taken together, our present data as well as previous findings suggest that inflammation or inflammatory cytokines may be involved in the entire process of soft-tissue calcification by CVB3 infection.…”
Section: Discussionsupporting
confidence: 86%
“…In response to vascular injury, the dedifferentiated VSMC increases osteogenic signaling through BMP-2, and BMP-2 is expressed in the atherosclerotic intima. 45 When VSMCs are cultured in serum from uremic patients, it results in increased Runx2 expression that is inhibited by the BMP-2 inhibitor, noggin. 46 Synthetic hydroxyapatite nanocrystals and isolated high-phosphate-induced nanocrystals have also been shown to upregulate the gene expression of BMP-2 and osteopontin in VSMCs, 31 thereby driving the vicious cycle of accelerated calcification.…”
Section: Cellular Mechanisms Of Calcium-and Phosphate-induced Calcifimentioning
confidence: 99%
“…One of these involves VSMCs or activated pericytes differentiating toward an osteogenic phenotype, mainly under the influence of bone morphogenic protein 2. 146,147 Bone morphogenic protein 2 is secreted by VSMCs and ECs, and its expression increases in advancing atherosclerotic plaques. In addition, calcification is linked to vascular inflammation and the influx of macrophages, which promote formation of microcalcifications and also induce VSMC differentiation.…”
Section: Calcificationmentioning
confidence: 99%